Tourism and COVID-19: Changes in Travel and Behavioral Patterns of Residents of Bosnia and Herzegovina - ČAUŠEVIĆ, Amra (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023DO - 10.14505/jemt.v14.4(68).07, 2023)
This paper analyses whether there have been any changes in the behavior and patterns of tourist travel after the outbreak of the COVID-19 pandemic. The convenience sample included 265 respondents. The results of the study show that the most important factors in choosing to travel during the COVID-19 pandemic are: cleanliness, safety, comfort, costs, and social distance. The results of the study show a statistically significant difference in the factors that influence choosing to travel during COVID-19 with regard to employment, i.e. , occupation, whereby the most factors when deciding on travel during COVID-19 are considered by pensioners and the least by students. When choosing a destination, as well as the image of the destination from the perspective of tourists, the study showed that owning a car is a statistically significant factor. The study also shows that there is a positive relationship that is statistically significant between the factors that influence choosing to travel during COVID-19 and the factors when choosing a destination from the perspective of tourists and the image of the destination, so those respondents who take into account more factors when choosing to travel during COVID-19, also take into account several factors when choosing a destination from the perspective of tourists and the image of the destination.